Remanufacturing and Evaluation of Al Zahrawiâ€™s Surgical instruments, Al Mokhdea as Scalpel Handle - Ahmadi, Seyedeh Aida; Zargaran, Arman; Mehdizadeh, Alireza; Mortazavi, Seyed Mohammad Javad (Galen Medical Journal, 2013)
Background: Current development of surgery is due to medical practitioners and surgeons practices and experiments throughout the history. Albucasis, the Muslim Spanish physician in 10 century AD was one of the pioneers in surgery that had major influence by his innovations in surgical techniques, treatment approaches and invention of instruments. He introduced a type of surgical knife named Mokhdea in his treaties, Al Tasreef that had mobile lancet. Material and Method: In this paper, we represent this historical instrument according to Albucasis points of view. Also, this knife was reproduced and finally a modified version of it was suggested for current using according to ancient knowledge. Results: Albucasis presented a retractable surgical knife with figure in the 30th volume of his book, Al Tasreef.Â  According to his description, this instrument was made including blade, clamp and handle. Also, a standardized new scale up surgical knife was suggested. This instrument includes a blade united with a lever that moves throughout a rail in the handle. Conclusion: The idea of making retractable surgical knife dates back to about 1000 years ago; presented by Muslim physician, Albucasis. Also, new presented surgical knife is better compared with current knives because of its comfortable using, safety and scale up.